2021
DOI: 10.1091/mbc.e20-10-0666
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 GTPase-activating proteins (GAPs) regulate generational inheritance of cell polarity and cell shape in fission yeast

Abstract: The highly conserved small GTPase Cdc42 regulates polarized cell growth and morphogenesis from yeast to humans. We previously reported that Cdc42 activation exhibits oscillatory dynamics at cell tips of Schizosaccharomyces pombe cells. Mathematical modeling suggests that this dynamic behavior enables a variety of symmetric and asymmetric Cdc42 activation distributions to coexist in cell populations. For individual wild type cells, however, Cdc42 distribution is initially asymmetrical and becomes more symmetric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…A recent report shows that presence of the GAPs at the cortex prevents local Cdc42 activation even upon localization of the scaffold Scd2, which recruits Scd1 to the cortex (Lamas et al, 2020b). Another report suggests that Cdc42 GAP levels in daughter cells determine the pattern of polarized growth in those cells (Pino et al, 2021). These reports and our findings together indicate that loss of Rga4 from the ends after mitosis is necessary to allow Cdc42 activation at these ends, so long as the MOR pathway is active.…”
Section: Discussionsupporting
confidence: 80%
“…A recent report shows that presence of the GAPs at the cortex prevents local Cdc42 activation even upon localization of the scaffold Scd2, which recruits Scd1 to the cortex (Lamas et al, 2020b). Another report suggests that Cdc42 GAP levels in daughter cells determine the pattern of polarized growth in those cells (Pino et al, 2021). These reports and our findings together indicate that loss of Rga4 from the ends after mitosis is necessary to allow Cdc42 activation at these ends, so long as the MOR pathway is active.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in fission yeast, vesicle insertion into the plasma membrane plays a positive role in CDC42 cluster formation by pushing the GAP Rga4 away from the center of the CDC42 cluster 177 . Interestingly, in the presence of negative feedback, the competition of two CDC42 clusters can change from antagonistic winner-takes-all to oscillatory, out-of-phase coexistence--the mechanism which was proposed to explain the discovery of the tip-to-tip CDC42-GTP oscillations in fission yeast 12,178,179 .…”
Section: [H2] Polarized Growth In Yeastsmentioning
confidence: 99%
“…In general, these GEFs colocalize with Cdc42 to activate Cdc42 locally ( Coll et al, 2003 ; Das et al, 2012 ; Kelly and Nurse, 2011 ). Inactivation of Cdc42 requires GAPs, and Cdc42 inactivation is a mechanism to prevent the spread of Cdc42-GTP to the non-growing regions of cells ( Das et al, 2012 ; Gallo Castro and Martin, 2018 ; Pino et al, 2021 ). In fission yeast, Rga3 ( Gallo Castro and Martin, 2018 ), Rga4 ( Tatebe et al, 2008 ), and Rga6 ( Revilla-Guarinos et al, 2016 ) have been identified as Cdc42 GAPs.…”
Section: Introductionmentioning
confidence: 99%